Penerapan Inhalasi Sederhana Menggunakan Daun Mint Terhadap Ketidakbersihan Jalan Nafas Pada Keluarga Ny. A Dengan TB Paru - Rismayanti Maimunah; Rachmawati, Kurnia (Nerspedia, 2023)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis by infecting the lungs and other organs in the body. Simple inhalation or evaporation method by giving mint leaf aroma therapy can be a solution to reduce shortness of breath. Case study of nursing care with pulmonary tuberculosis in the family of Mrs. A against airway obstruction through the application of simple inhalation with mint leaves for 3 days  Complementary therapy with simple inhalation using mint leaf aromatherapy given for 3 days showed a decrease in respiratory frequency and dyspnea in patients with pulmonary tuberculosis.